PROJETO COLMEIA (CIPEEX, 2025)
Projeto ColmeiaSofia Silva Vieira D'Abadia,Carlos Eduardo Silva Costa,Letícia de Fatima Barcelos Porto,Camilly Christine Sacch Floriano,Henrique Valle de Lima.In the realm of non-profit organizations dedicated to supporting cancer patients, Projeto Colmeia stands out for its vital role in providing essential services and assistance. Despite its crucial mission, the institution faces significant operational and technical challenges that hinder its effectiveness and outreach. Recognizing the need for enhanced communication and public engagement, a comprehensive evaluation was conducted to assess these challenges and to inform the development of an integrative project aimed at bolstering the institution’s impact. The primary objective of the visit was aimed at understanding the institution’s operational and technical challenges and gathering information to support the development of an integrative project. This in-person visit aimed to gather information for the project’s development. The methodology included initial meetings with institutional representatives, stakeholder interviews, facility inspections, document analysis, and for the development, Rapid Prototyping, User Research and Analysis, and Waterfall Method. A significant need identified was the development of a comprehensive website to enhance communication and visibility. Key findings highlighted the necessity for a detailed website that includes information about the institution's history, activities, volunteer opportunities, and event schedules. This website aims to improve public engagement, facilitate donations, and streamline volunteer involvement. The intervention will focus on enhancing the institution's online presence to facilitate better community interaction and support. The next steps involve drafting a detailed project vision, planning the development process, Content Creation and Refinement and Iteration to validate the proposed solutions.
Keywords: projeto colmeia; nonprofit organization; website development; community engagement